Low-volume leukapheresis in non-cytokine-stimulated donors for the collection of mononuclear cells - Anyanwu, Adamma; Sitzmann, Nicole; Hetjens, Svetlana; Klüter, Harald; Wuchter, Patrick (Transfusion medicine and hemotherapy, 2018)
Background: There is an increasing demand for products containing mononuclear cells (MNCs) for cellular immune therapy. Hence, leukapheresis is increasingly performed in healthy volunteer donors. Methods: We evaluated 147 low-volume leukapheresis procedures from 77 healthy non-cytokine-stimulated donors. Complete blood counts (CBCs) of the donors were measured before and directly after the procedures as well as from the MNC products. Follow-up CBCs were collected from donors within 21 days. Results:The product hematocrit within a range from 1.2 to 6.0% did not correlate with the collection efficiency of any cell population or the granulocyte and platelet yield. There was a strong correlation between the CBC values before leukapheresis and the cell yield of lymphocytes and monocytes as well as a perfect negative correlation between cell recruitment and cell loss in all cell populations. Furthermore, we observed a significant decrease in the CBC values in all cell populations directly after leukapheresis, which recovered within a mean of 16.1 days (SD ± 2.1 days) and even showed a significant increase in granulocytes and platelets. Conclusion: Low-volume leukapheresis is feasible for the collection of MNCs in which the product hematocrit is negligible for the collection efficiency, cell yield, or contamination of residual cells under operational settings recommended by the manufacturer. Our data suggests that cell recruitment is regulated by the number of cells removed, which may also be the stimulus to induce granulo- and thrombopoiesis within the first days after leukapheresis.